An Analysis of Cultural Stereotypes in an Indonesian Government-Endorsed ELT Textbook - Nizar, Rifka Indah; Prasetya, Willy (IJELR: International Journal of Education, Language, and Religion, 2024)
Cultural stereotypes in English Language Teaching (ELT) textbooks may influence how students shape their perspectives towards the cultures being studied, yet little research discusses how cultural stereotypes emerge in ELT textbooks. This study aimed to describe the cultural stereotypes in an ELT textbook published by the Indonesian government. The book being analyzed was entitled English for Nusantara SMP/MTs KELAS VII for the seventh grade of junior high school. The data were collected and analyzed through content analysis to point out the valid inference. The findings showed that cultural stereotypes were depicted in the textbook in several ways: appearance, gender, behavior, and lifestyle. This study may provide an insight into how cultural stereotypes are depicted in the textbook, and it may contribute practically for textbook designers or material developers to take into account how cultural values will be included into textbook in order to avoid creating stereotypes for a particular culture. Furthermore, this study may also help the teachers take into account cultural stereotypes in designing and selecting learning materials for students.